2012
DOI: 10.18388/abp.2012_2104
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a polyclonal antibody against hypericin synthase and localization of the enzyme in red-pigmented Hypericum perforatum L. plantlets.

Abstract: Hypericum perforatum is well known for its antidepressant and anti-inflammatory activities, for which hypericin and its derivatives are indicated to be the most active compounds. Hypericin synthase (Hyp-1) is the only protein proven to catalyze the synthesis of hypericin. In this study, the full-length cDNA of Hyp-1 was chemically synthesized according to the Hyp-1 sequence in Gen-Bank (accession no. AY148090) and then cloned into the plasmid pET22b. Hyp-1 was expressed in Escherichia coli BL21 (DE3) and purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…In the present study, equal amounts of the Hyp-1 protein were found in leaf margin and leaf interior parts and, thus, neither our results provide any evidence that the Hyp-1 protein would be specifically associated or accumulating via transportation to the dark glands for its activity in the final stages of hypericin biosynthesis as suggested earlier ( Bais et al, 2003 ). Our results are in agreement with the earlier study of Qian et al (2012) who reported the presence of the Hyp-1 protein in leaf, stem and root of H. perforatum with no association in dark glands in leaves. These findings question the role of the hyp-1 as a key gene in the hypericin biosynthesis.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, equal amounts of the Hyp-1 protein were found in leaf margin and leaf interior parts and, thus, neither our results provide any evidence that the Hyp-1 protein would be specifically associated or accumulating via transportation to the dark glands for its activity in the final stages of hypericin biosynthesis as suggested earlier ( Bais et al, 2003 ). Our results are in agreement with the earlier study of Qian et al (2012) who reported the presence of the Hyp-1 protein in leaf, stem and root of H. perforatum with no association in dark glands in leaves. These findings question the role of the hyp-1 as a key gene in the hypericin biosynthesis.…”
Section: Discussionsupporting
confidence: 94%
“…The parenchyma cells in vascular tissue attend to the lateral transport of compounds, while the pericycle cells are known to be metabolically active and involved in the transport of compounds to and from the vascular bundle that they surround. Our results of the hyp-1 transcript localization are in agreement with the data obtained by Qian et al (2012) who studied the cellular location at protein level in H. perforatum tissues and found the Hyp-1 protein to be present mainly in vascular tissues of both root and stem as well as in leaf mesophyll with no obvious signal in dark glands.…”
Section: Discussionsupporting
confidence: 92%
“…Polyclonal AK-specific antiserum was generated at Xiamen University in the Laboratory Animal Centre, as described by Qian et al (2012). The polyclonal rabbit anti-AK antiserum was purified by affinity chromatography on Protein A Sepharose (GE Healthcare, New York, NY, USA).…”
Section: Preparation Of Rabbit Anti-ak Iggmentioning
confidence: 99%
“…The latter hypothesis was corroborated by genetic data, which showed that hyp-1 has gene structure analogous to typical pr-10 genes ( Kosuth et al, 2013 ), but it has to be underlined that Hyp-1 has not been demonstrated so far to be involved in stress response of H. perforatum . With regard to the localization in the plant, it was shown that Hyp-1 mRNA expression occurs in all organs of Hypericum seedlings with the highest levels in roots ( Kosuth et al, 2007 ), whereas immunofluorescence assays of plantlets revealed wide distribution of the Hyp-1 protein in different tissues, including roots, stem, and leaves ( Qian et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%